Evaluation on the performance of sustainable wire arc additive manufacturing using micro plasma arc welding - Rosli, Nor Ana; Alkahari, Mohd Rizal; Mohamad Norani, Mohamad Nordin; Abdollah, Mohd Fadzli bin; Paijan, Lailatul Harina; Furumoto, T (2023)
Metal additive manufacturing has gained popularity due to its significant advancement in minimising waste. The product design using additive manufacturing (AM) does not require mould and less material required, which is less waste. In this way, AM has the potential to transform the manufacturing industries towards greater sustainability. Besides, AM allow more complex designs and shape than conventional manufacturing. Wire arc additive manufacturing (WAAM) is one of the most popular metal AM that has received significant attention due to its usefulness for localising, repairing, and modifying instead of discarding and replacing entire components. However, conventional welding technology faced the issue of significant heat input, low surface quality, and low dimensional accuracy of WAAM components. Micro-plasma arc welding (MPAW) is a new alternative to the WAAM process. The speciality of MPAW is low current provided of 1A to 25A current range, leading to low heat input and energy-efficient